2020
DOI: 10.1111/nph.16541
|View full text |Cite
|
Sign up to set email alerts
|

Chloride involvement in the synthesis, functioning and repair of the photosynthetic apparatusin vivo

Abstract: Summary Cl− has long been known as a micronutrient for oxygenic photosynthetic resulting from its role an essential cofactor for photosystem II (PSII). Evidence on the in vivo Cl− distribution in Spinacia oleracea leaves and chloroplasts shows that sufficient Cl− is present for the involvement in PSII function, as indicated by in vitro studies on, among other organisms, S. oleracea PsII. There is also sufficient Cl− to function, with K+, in parsing the H+ electrochemical potential difference (proton motive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…Particularly important in the current context is the similarity of the response to photoinhibition by photosynthetically active radiation to that in other cyanobacteria (Sicora et al 2008;Koyama et al 2008;Bernát et al 2012;Mulo et al 2012;Cardona 2015Cardona , 2016. Raven (2020) points out that, if the Cl − concentration needed for assembly of the Mn 4 CaO 5 oxygen-evolving complex is the same as that needed by PSII of isolated Spinacia (Vinyard et al 2019), the rate of assembly would be very significantly restricted when the growth medium for Gloeobacter was BG11; Sicora et al (2008) found about 30% recovery from photoinhibition by photosyntheticaly active radiation in 2 hours in BG11 medium. Vinyard et al (2019) provide information on the concentration of Mn and Ca needed for the maximum rate of OEC assembly in PSII in Spinacia, and these are compared below with the concentrations of Mn and Ca in BG11.…”
Section: Synthesis Repair and Operation Of The Photosynthetic Apparatus Of Gloeobacter In Relation To Its Low-salinity Habitatmentioning
confidence: 99%
“…Particularly important in the current context is the similarity of the response to photoinhibition by photosynthetically active radiation to that in other cyanobacteria (Sicora et al 2008;Koyama et al 2008;Bernát et al 2012;Mulo et al 2012;Cardona 2015Cardona , 2016. Raven (2020) points out that, if the Cl − concentration needed for assembly of the Mn 4 CaO 5 oxygen-evolving complex is the same as that needed by PSII of isolated Spinacia (Vinyard et al 2019), the rate of assembly would be very significantly restricted when the growth medium for Gloeobacter was BG11; Sicora et al (2008) found about 30% recovery from photoinhibition by photosyntheticaly active radiation in 2 hours in BG11 medium. Vinyard et al (2019) provide information on the concentration of Mn and Ca needed for the maximum rate of OEC assembly in PSII in Spinacia, and these are compared below with the concentrations of Mn and Ca in BG11.…”
Section: Synthesis Repair and Operation Of The Photosynthetic Apparatus Of Gloeobacter In Relation To Its Low-salinity Habitatmentioning
confidence: 99%
“…SLC4 HCO 3 À transporters are known from the genomes of a species of the (present) Symbiodiniaceae (Aranda et al 2016), Alexandrium monilatum and Prorocentrum minimum (Hennon et al 2017) and Thoracosphaera heimii (Van de Waal et al 2013e Waal et al 2013; presumably these are expressed in the plasmalemma. The various SLC4 HCO 3 À transporters can be Na + :HCO 3 À symporters or HCO 3 À :Clantiporters; work on the dinoflagellate SLC4 is needed to determine the co-or counter-ions, and their stoichiometry (Liu et al 2015, Raven 2020, Raven and Beardall 2020, and hence the possibility that this transporter brings about active HCO 3 À influx with corresponding accumulation of HCO 3 À in the cytosol. For the organisms in which CO 2 is a major inorganic C species entering the cell, and possibly when HCO 3 À enters the cell, active HCO 3 À influx into the plastid is needed.…”
Section: Mechanisms Of Active Transport Of Inorganic Cmentioning
confidence: 99%
“…The various SLC4 HCO 3 − transporters can be Na + :HCO 3 − symporters or HCO 3 − :Cl ‐ antiporters; work on the dinoflagellate SLC4 is needed to determine the co‐ or counter‐ions, and their stoichiometry (Liu et al. 2015, Raven 2020, Raven and Beardall 2020), and hence the possibility that this transporter brings about active HCO 3 − influx with corresponding accumulation of HCO 3 − in the cytosol. For the organisms in which CO 2 is a major inorganic C species entering the cell, and possibly when HCO 3 − enters the cell, active HCO 3 − influx into the plastid is needed.…”
Section: Mechanisms Of Active Transport Of Inorganic Cmentioning
confidence: 99%
“…Here the acidic and electropositive compartment is the thylakoid lumen, and potassium channels, and also chloride channels, regulate the components of the PMF, with important implications for other photosynthetic processes. [5] ACKNOWLEDGEMENT The University of Dundee is a registered Scottish Charity, SC015096.…”
Section: Origin Of the Roles Of Potassium In Biologymentioning
confidence: 99%
“…the cyanobacterium Gloeobacter , with photosynthetic, respiratory and proton‐pumping rhodopsin‐based chemiosmotic coupling at the plasma membrane. [ 5 ] These principles also apply to regulating the PMF in chemiosmotic coupling at the plasma membrane of [ 5 ] intracellular membranes such as the membrane separating the thylakoid lumen from the cytosol of cyanobacteria other than Gloeobacter , and the chloroplast stroma of eukaryotic oxygenic photosynthetic organisms. Here the acidic and electropositive compartment is the thylakoid lumen, and potassium channels, and also chloride channels, regulate the components of the PMF, with important implications for other photosynthetic processes.…”
mentioning
confidence: 99%